CAN BLENDED LEARNING HELP IMPROVE STUDENTS' CRITICAL THINKING SKILLS? - Syaiful Anwar; Wahyu Setyaningrum (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The flow of information is currently spreading very quickly, and massively, so critical thinking skills are needed to obtain valid information. Based on the 2015-2019 Ministry of Education and Culture Strategic Plan, learning activities in Indonesia have not yet facilitated the development of students' critical thinking skills. One of the lessons that are thought to be able to improve student's critical thinking skills is blended learning (BL). Therefore, this experimental study aims to determine the effectiveness of BL in terms of students' critical thinking skills. Data were collected through written tests and interviews. This study involved 68 eighth-grade junior high school students. The main instrument in this study is a mathematics test (pre-test and post-test) which consists of five essay questions. The independent sample t-test was used to compare the difference in average scores between the experimental class and the control class, followed by using the normalized gain (n-gain) score from the pretest and posttest to test the effectiveness of BL in terms of students' critical thinking skills. Based on the independent sample t-test, there is a significant difference in the average value of critical thinking skills between the BL class and the conventional class. The average n-gain score for the experimental class (BL) is categorized as less effective. The average n-gain score for the control class (conventional) is included in the ineffective category. So in conclusion, the application of BL in mathematics learning is categorized as less effective in terms of critical thinking skills.